2002
DOI: 10.1124/dmd.30.3.319
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Human Cytochromes P450 Responsible for Atomoxetine Metabolism

Abstract: ABSTRACT:Studies were performed to determine the human enzymes responsible for the biotransformation of atomoxetine to its major metabolite, 4-hydroxyatomoxetine, and to a minor metabolite, N-desmethylatomoxetine. Utilizing human liver microsomes containing a full complement of cytochrome P450 (P450) enzymes, average K m and CL int values of 2.3 M and 103 l/min/mg, respectively, were obtained for 4-hydroxyatomoxetine formation. Microsomal samples deficient in CYP2D6 exhibited average apparent K m and CL int va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
184
4
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(198 citation statements)
references
References 7 publications
7
184
4
3
Order By: Relevance
“…As described by some authors, CYP2D6, CYP2C19, CYP2C9, CYP3A4, and CYP3A5 involved in the biotransformation of R-and S-fluoxetine to their N-desmethyl metabolites [65,66]. It was also demonstrated that CYP2C9 catalyzes R-fluoxetine demethylation and the formation of S-norfluoxetine is highly dependent on CYP2D6 [65,67].…”
Section: Fluoxetinementioning
confidence: 99%
See 1 more Smart Citation
“…As described by some authors, CYP2D6, CYP2C19, CYP2C9, CYP3A4, and CYP3A5 involved in the biotransformation of R-and S-fluoxetine to their N-desmethyl metabolites [65,66]. It was also demonstrated that CYP2C9 catalyzes R-fluoxetine demethylation and the formation of S-norfluoxetine is highly dependent on CYP2D6 [65,67].…”
Section: Fluoxetinementioning
confidence: 99%
“…It was also demonstrated that CYP2C9 catalyzes R-fluoxetine demethylation and the formation of S-norfluoxetine is highly dependent on CYP2D6 [65,67]. Their catalytic activities depend on genetic polymorphisms.…”
Section: Fluoxetinementioning
confidence: 99%
“…A recent meta-analysis reported the number-needed-to-treat (NNT) for atomoxetine treatment response (reduction of Ն25% in ADHD-RS total score from baseline) was 3.43 (95% CI, 2.79-4.45). 18 Signifi cant improvement compared with those treated with placebo has been demonstrated across efficacy measures, in younger (6-7 years) and older (8)(9)(10)(11)(12) However, overall in the treatment of pediatric ADHD, superior effect sizes are consistently observed with immediate-release and long-acting stimulants, as compared to non-stimulants, including atomoxetine. 20 …”
Section: Atomoxetine For Adhd In Children and Adolescentsmentioning
confidence: 99%
“…13,14) However, it is unclear whether CYP3A4 and CYP3A5 share the metabolic pathway of tadalafil because no systematic study on the CYP3A isoforms involved in the demethylenation of the drug has been reported in the literature to date.…”
Section: )mentioning
confidence: 99%